On global weak solutions to the Cauchy problem for the Navier–Stokes equations with large L3-initial data. (May 2017) - Seregin, G.; Šverák, V.
Abstract: The aim of the note is to discuss different definitions of solutions to the Cauchy problem for the Navier–Stokes equations with the initial data belonging to the Lebesgue space L 3 ( R 3 )